Pulse formation and dynamics in self-pulsating semiconductor laser diodes - Lynch, Stephen A. (Trinity College (Dublin, Ireland). School of Physics, 2000)
Self-pulsating lasers emitting at 800 nm are used in compact disc (CD) players because their low coherence makes them relatively insensitive to optical feedback. The ever increasing demand for higher capacity storage on optical discs necessitates the move to shorter wavelengths. However, attempts at achieving self-pulsation at shorter wavelengths have met with limited success. This suggests that the physical understanding of self-pulsation in semiconductor lasers is incomplete. The effect of temperature on the processes which control self-pulsation in infrared CD lasers is explored. The variation of self-pulsation frequency with bias current was found to be highly independent of temperature, which means that charge carrier diffusion does not play a first order role. A rate equation model incorporating temperature related effects was developed to explain these results.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin